Sensemaking in OrganizationsSensemaking in Organizations, by WeickKarl E. Thousand Oaks, CA: Sage. - Paul, Shrivastava; Gioia, Dennis A.; Mehra, Ajay (Academy of Management Review, 1996)
The article reviews the book ?Sensemaking in Organizations,? by Karl E. Weick.